Efecto del uso del inhibidor de síntesis de giberelinas paclobutrazol en el rendimiento del cultivo del maíz (Zea mays L.) sometidos a altas densidades de siembra - Sánchez Álvarez, Darwin Roberto (2022)
The research was carried out at the "La María" Campus of the State Technical University of Quevedo, for which two hybrids and a native variety of corn (Zea mays L.) were used, with and without the application of a growth regulator Paclobutrazole, this input being capable of inhibiting gibberellins, hormones responsible for growth. The objectives of the research were: to determine the effect of the use of the inhibitor of synthesis of gibberellins Paclobutrazole on the yield of corn, to determine the height and diameter of the stem during the vegetative stage, to quantify the yield of the grains, to perform an economic analysis.